The Effect of Social Capital on Decision Making for Welfare of Micro Business Women in Korem Kendari Market - Jamaluddin, Nurrahmah; La Ola, Taane; Limi, Muhammad Aswar (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2019)
The aim to be achieved in this study was to determine the effect of social capital on decision making for the welfare of micro-business women in the Kendari Korem Market. Location of research at Kendari Korem Market. The population in this study were all Micro Business Women who work as vegetable sellers at Kendari Korem Market, which numbered 115 people and the sample determination used Slovin formula as many as 50 people. The method used in sampling is done by Simple Random Sampling. The variables observed in this study were the identity of the respondents in this study, namely age, education level, number of family dependents, business experience. Social capital variables that include trust (trust), network (social network), norms (norms) that exist in the community/self someone. Data analysis in this study used covariant-based structural equation modeling analysis. Based on the results of the study it can be concluded that the trust and network of micro businesswomen in the Kendari Korem Market directly influence the decision making and norms of micro-business women not to have an influence on decision making. Based on the results of the study, it is recommended that micro businesswomen in the korem kendari market increase the values of social capital in decision making to improve their welfare